Peningkatan Kemampuan Menganalisis Makna Kebahasaan Teks Biografi dengan Menggunakan Model Pembelajaran Jigsaw Siswa Kelas X SMK Negeri 1 Gunungsitoli - Leni Putri Harefa; Arozatulo Bawamenewi (Universitas Nias, 2023)
The problem in this study is that students are less able to analyze language in biographical texts. Therefore, researchers apply the Jigsaw learning model to overcome this problem. The purpose of this lesson is to improve students' ability to analyze language in biographical texts using the Jigsaw model. The subjects of this study were the tenth grade students of SMK Negeri 1 Gunungsitoli, totaling 24 people, 14 boys and 10 girls. This research uses classroom action assessment (PTK) with the implementation procedures are planning, action, observation and reflection. From the results of the study, the values obtained in cycle I with the lowest value were 30 and the highest value was 90 with an average value of 62.08% and in cycle II the lowest value was 60 and the highest value was 95 with an average value of 86.45%. The results of observations of students in the first cycle of the first meeting with an average value of 62.17% and the second meeting 70.19% and the second cycle of the first meeting with an average value of 84.73% and the second meeting 91.34%. The results of observations of researchers in cycle I first meeting with an average value of 61.54% and the second meeting 69.23% and in cycle II the first meeting with an average value of 83.33% and the second meeting 92.30%. Based on this research, it can be concluded that using the Jigsaw learning model can improve the ability to analyze aspects of linguistic meaning in biographical texts in class X SMK Negeri 1 Gunungsitoli 2022/2023 Academic Year.